The Private/Public Security Nexus in China - Trevaskes, Susan (Social justice, 2007)
A study was conducted to examine the complex relationship between the public and private security sectors in China. Data were obtained from media stories concerning private security companies and a review of the literature. Findings revealed that in the last 20 years, private security firms in China have been expected to fulfill the dual requirements of being profitable and serving the public interest by preventing crime and, more controversially, putting down public order disturbances. Findings indicated that this duality of purpose mirrors a delicate balance between permissiveness and repression; supply and demand have fused the public/private security nexus together. Findings suggested that the private security industry in China will be subject to greater market forces in the future, and the police force will move from supervision to regulation. Findings are discussed in detail.